Plant Extracts as Seed Dressing to Control Bacterial Blight of Long-Staple Cotton Seedlings. Issue 1 (2nd January 2016) - Popoola, A. R.; Ganiyu, S. A.; Awotide, O. G.; Oduwaye, A. O.
ABSTRACT: Xanthomonas axonopodis pv. malvacearum (Smith) Dye ( Xam ) causes bacterial blight of cotton ( Gossypium hirsutum L.) with a yield loss of up to 50% in Nigeria. Continuous and indiscriminate application of chemical pesticides, with its attendant health hazards, has necessitated the search for an environment-friendly method of control. Cold water extracts from leaves of Lawsonia inermis, Aloe vera, and Azadirachta indica were screened for their effectiveness in the control of Xam in vitro and in screen house. The treatments were three leaf extracts and three concentrations (50, 25, and 12.5% w/v) of each extract. Oxytetracycline (at 1/100th concentration of explants) served as a positive control and sterile distilled water as negative control. The crude extracts and the control were applied on long-staple cotton ( Gossypium barbadense, SAMCOT-11) as seed dressing. Results showed the least bacterial count of 1.2 × 10 7 cfu/ml in plates containing Lawsonia inermis at a concentration of 12.5%. Both L. inermis and A. indica had highest seedling emergence of 62.5% at a concentration of 12.5%. Application of 50% concentration of L. inermis and A. indica significantly reduced the occurrence of bacterial blight on the cotton seedlings. L. inermis supported the highest seedling vigor-index of 1, 095.06 and 1, 237.50 at 50 and 25% levels, respectively. L. inermis could be a suitable plant extract at 50% w/v concentration for the control of bacterial seedling blight of G. barbadense in screen house.